A brinquedoteca e sua potencialidade para o desenvolvimento da infância - Rodrigues, Brenda Leyre Oliveira da Silva (2022)
The dissertation entitled " The toy library and its potential for childhood development " is linked to the line of research "Training, Professional Development for Teachers, and Educational Work" " of the Graduate Program in Education (PPGE), Faculty of Education (FE), Federal University of Goiás (UFG). It is part of the set of research carried out by REDECENTRO Network of Researchers on Teachers from Midwest/Brazil. The toy library is the essentially ludic and formative locus, prepared and organized to awaken different modes of ludicity, especially free play. For this reason, the toy library is not restricted to just one space, since it is necessary to have a trained and qualified professional to plan, guide and promote recreational training opportunities. With regard to childhood, we understand that the toy library allows the child to cultivate culture, exercise their freedom, ludicity and creativity, thus, in this place, they are recognized as a subject of rights, especially the act of playing. In this sense, it is assumed here as a research topic that gives centrality to the construction of historicity and theoretical deepening from the analysis of works published in the National Association of Graduate Studies and Research in Education (ANPEd), from 2012 to 2021. This choice is justified by the relevance of this scientific environment, where theoretical and academic works in the field of education are located. It highlights the recent productions of the academic community, used as training material. Therefore, our general objective is to understand the discursive meanings given to the concept of toy library in the works of ANPEd, and in the dialogue with the authors who dealt with the subject, we seek to understand the meaning given to the concept. The specific objectives are: 1) to build the historicity of childhood; 2) theoretically build the concept of toy library and its articulation to the recognition of conditions for children as subjects of rights; 3) identify the ANPEd in the production, themes that are related to the toy library concept, such as: playing, toys and the ludic. We developed a bibliographic research, with a qualitative approach, based on the dialectical method. The result of the research showed that the subject was divided into numerous work groups, articulating the themes: play, toy and games, showing that despite the lack of a literal presentation of the toy library in the association, it is tacit agreement that this space is expressed as a necessary place for the “good development of the child”.